Holy Wars or Holy Alliances : the Return of Religion to the Global Political Stage - Graziano, Manlio (Religion, Culture, and Public Life, 2017)
Religions are creeping back into the social, political, and economic spheres previously occupied by secular institutions and ideologies. Disillusioned with industrial progress and cut off from opportunity and wealth, many are looking to Buddhism, Judaism, Islam, and Christianity to restore a sense of purpose not found in daily life. Since the 1970s, the Catholic Church has sought a "holy alliance" among the world's religions to recentralize religious ideas and practice in modern society. Holy Wars or Holy Alliances explores the nation-state's current crisis to better understand its origins and future development. Focusing on the Catholic Church, Manlio Graziano looks at how Catholicism has coordinated world religions in joint actions. Through its material, financial, and institutional strength, the Church has gained power and increased its profile in international politics. Challenging the ideas that modernity is tied to progress and religion necessarily means decline, Graziano documents the "return" or the "revenge" of God in all facets of secular life. He shows that tolerance, pluralism, democracy, and science have not triumphed as claimed in modern times. To fully grasp the destabilizing dynamics at work in our world today, Graziano argues, we must appreciate the nature of the religious struggles and political holy wars now unfolding across the international stage.